Role of Toll-Like Receptors in Actuating Stem/Progenitor Cell Repair Mechanisms: Different Functions in Different Cells - Fabio Sallustio; Claudia Curci; Alessandra Stasi; Giuseppe De Palma; Chiara Divella; Roberto Gramignoli; Giuseppe Castellano; Anna Gallone; Loreto Gesualdo (Hindawi Limited, 2019)
Toll-like receptors (TLRs) represent one of the bridges that regulate the cross-talk between the innate and adaptive immune systems. TLRs interact with molecules shared and preserved by the pathogens of origin but also with endogenous molecules (damage/danger-associated molecular patterns (DAMPs)) that derive from injured tissues. This is probably why TLRs have been found to be expressed on several kinds of stem/progenitor cells (SCs). In these cells, the role of TLRs in the regulation of the basal motility, proliferation, differentiation processes, self-renewal, and immunomodulation has been demonstrated. In this review, we analyze the many different functions that the TLRs assume in SCs, pointing out that they can have different effects, depending on the background and on the kind of ligands that they recognize. Moreover, we discuss the TLR involvement in the response of SC to specific tissue damage and in the reparative processes, as well as how the identification of molecules mediating the differential function of TLR signaling could be decisive for the development of new therapeutic strategies. Considering the available studies on TLRs in SCs, here we address the importance of TLRs in sensing an injury by stem/progenitor cells and in determining their behavior and reparative activity, which is dependent on the conditions. Therefore, it could be conceivable that SCs employed in therapy could be potentially exposed to TLR ligands, which might modulate their therapeutic potential in vivo. In this context, to modulate SC proliferation, survival, migration, and differentiation in the pathological environment, we need to better understand the mechanisms of action of TLRs on SCs and learn how to control these receptors and their downstream pathways in a precise way. In this manner, in the future, cell therapy could be improved and made safer.